Proactive condition monitoring of low-speed machines - Stamboliska, Zhaklina; Rusinski, Eugeniusz; Moczko, Przemyslaw; SpringerLink (Online servi (Cham Springer, 2015)
This book broadens readers' understanding of proactive condition monitoring of low-speed machines in heavy industries. It focuses on why low-speed machines are different than others and how maintenance of these machines should be implemented with particular attention. The authors explain the best available monitoring techniques for various equipment and the principle of how to get proactive information from each technique. They further put forward possible strategies for application of FEM for the detection of faults and technical assessment of machinery. Implementation phases are described and industrial case-studies of proactive condition monitoring are included. Proactive Condition Monitoring of Low-Speed Machines is an essential resource for engineers and technical managers across a range of industries as well as design engineers working in industrial product development. This book also: · Explains the practice of proactive condition monitoring and illustrates implementation phases · Presents a detailed discussion of best techniques for proactive condition monitoring specifically for low-speed machines · Demonstrates application of finite element modeling for successful proactive condition monitoring · Broadens readers? contextual understanding with case-studies related to applications of proactive condition monitoring in heavy indus
1 Introduction -- Review of Today's Industry and Role of Condition Monitoring; Abstract; References; 2 Maintenance Management and Applied Strategies; 3 Condition Monitoring Considerations for Low-Speed Machines; 4 Proactive Condition Monitoring of Low-Speed Machines; 5 Condition Monitoring Techniques for Low-Speed Machines; Abstract; 6 FEM in Proactive Condition Monitoring; 7 Case Studies of Proactive Condition Monitoring Applications.
Electronic reproduction.
Keywords: Machinery -- Monitori; Electronic boo